INVESTIGATING CRITICAL PEDAGOGY IN THE DEVELOPMENT OF THE PESANTREN EDUCATION SYSTEM - Bina Adi Prakosa; Triana Rejekiningsih; Akhmad Arif Musadad (Green Publisher, 2023)
Critical pedagogy perspectives are currently being promoted in educational technology to advocate inclusion and social justice. However, little has been considered about the prospects of implementing it in the pesantren (Islamic boarding schools) education system. This research investigates the contribution of Paulo Freire's ideas in developing the pesantren as an indigenous Indonesian educational institution that has experienced marginalization. The study used a semi-systematic or narrative review to examine various theoretical literature and empirical research, then analyzed all source materials using content analysis techniques. The findings reveal that pesantren has developed Freirean critical pedagogy in adult education training to increase critical awareness, encourage civil society participation, break the culture of silence, and communicate people's aspirations through various media and technologies. The study identifies gaps between critical pedagogy and educational technology in general. Still, it gives justifications about prospects to encourage further research and development in Islamic pesantren education settings in Indonesia.